Meningeal inflammatory response and fibrous tissue remodeling around intracortical implants: An in vivo two-photon imaging study. (March 2019) - Eles, J.R.; Vazquez, A.L.; Kozai, T.D.Y.; Cui, X.T.
Abstract: Meningeal inflammation and encapsulation of neural electrode arrays is a leading cause of device failure, yet little is known about how it develops over time or what triggers it. This work characterizes the dynamic changes of meningeal inflammatory cells and collagen-I in order to understand the meningeal tissue response to neural electrode implantation. We use in vivo two-photon microscopy of CX3CR1-GFP mice over the first month after electrode implantation to quantify changes in inflammatory cell behavior as well as meningeal collagen-I remodeling. We define a migratory window during the first day after electrode implantation hallmarked by robust inflammatory cell migration along electrodes in the meninges as well as cell trafficking through meningeal venules. This migratory window attenuates by 2 days post-implant, but over the next month, the meningeal collagen-I remodels to conform to the surface of the electrode and thickens. This work shows that there are distinct time courses for initial meningeal inflammatory cell infiltration and meningeal collagen-I remodeling. This may indicate a therapeutic window early after implantation for modulation and mitigation of meningeal inflammation.